2012
DOI: 10.1002/wene.54
|View full text |Cite
|
Sign up to set email alerts
|

Technology cooperation for sustainable energy: a review of pathways

Abstract: Policy makers, practitioners and academics agree that addressing climate change requires global efforts and that one pillar of any effective approach must include actions undertaken by developing countries. A key mechanism in which developing countries can be engaged is through collaboration to elicit more use of sustainable energy technologies in a region, organization, or community's energy portfolio. Approaches have tended to emphasize the role of the public and / or private sector. An alternative view has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Discourse, meaning written and spoken communications by actors, can promote actors' efforts to tackle societal issues that need to be resolved in order to achieve a better society [23][24][25][26]30]. The discovery of actors in the texts is becoming increasingly important to research on social innovation.…”
Section: Narrow Renewable Energymentioning
confidence: 99%
See 2 more Smart Citations
“…Discourse, meaning written and spoken communications by actors, can promote actors' efforts to tackle societal issues that need to be resolved in order to achieve a better society [23][24][25][26]30]. The discovery of actors in the texts is becoming increasingly important to research on social innovation.…”
Section: Narrow Renewable Energymentioning
confidence: 99%
“…Socio-technical transition focused on energy involves interaction and interplay between actors [2][3][4], which produces discourse [7,8]-a variety of written and spoken communication. Such discourse reaches a social consensus about proactively coping with societal issues and challenges [23][24][25][26]30] by gaining more prominent status in the national energy and industrial system and consistently expands the discourse related to renewable energy [93]. In the context of a discourse on the transition to a renewable-energy-based economy, we explore and interpret the structural features of the contexts, in which the keyword is discussed and understood in discourses [111].…”
Section: Appendix Ementioning
confidence: 99%
See 1 more Smart Citation
“…Governments, development banks, bilateral and multilateral agencies, private enterprises and non-governmental organisations (NGOs) all engage in international development assistance for renewable energy, often with a special emphasis on off-grid rural electrification and small-scale applications for populations lacking access to modern energy services (Chaurey et al, 2012;Sovacool and Drupady, 2012). However, as many RET initiatives fail to achieve sustainable outcomes, a growing body of literature has identified barriers and drivers to the adoption of RETs (Bhattacharyya, 2012;El Fadel et al, 2013;Mallett, 2013;Palit and Chaurey, 2011;Sovacool and Drupady, 2012). Academic reviews and practitioner evaluations suggest that the sustainability and impact of RET interventions to a large extent depend on:…”
Section: Development Assistance For Off-grid Rets: Lessons Learntmentioning
confidence: 99%
“…3 Case studies of development interventions aiming at the adoption of off-grid RETs reported mixed outcomes, with the impact and sustainability of international programmes being inhibited by persistent resource, capacity and participation gaps (Bhattacharyya, 2012;Kruckenberg, 2015;Kumar et al, 2009;Sovacool and Drupady, 2012). North-South partnerships between organisations with complementary resources and expertise are seen as having the potential to bridge some of these gaps, and they are thought to play an important role in the creation of alternative low-carbon development pathways (Chaurey et al, 2012;Fernández-Baldor et al, 2012;Forsyth, 2012;Kruckenberg, 2015;Mallett, 2013;Morsink et al, 2011). However, it has been shown that the performance 1 The terms 'Global South'/'Southern' and 'Global North'/'Northern' refer to the inequalities existing between the Northern and Southern hemispheres.…”
Section: Introductionmentioning
confidence: 99%